2022
DOI: 10.3389/fnut.2022.980429
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of an extra virgin olive oil enriched mediterranean diet on metabolic syndrome: Lights and shadows of a nutraceutical approach

Abstract: For years it has been established that the only truly effective treatment of metabolic syndrome (MS) is lifestyle modification to prevent its cardiovascular (e.g., coronary artery disease and atherosclerosis), metabolic (e.g., diabetes mellitus), and hepatic (e.g., steatosis and non-alcoholic steatohepatitis) complications. The focal points of this approach are to increase physical activity and intake of a diet characterized by high quantities of fruits, vegetables, grains, fish, and low-fat dairy products, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 102 publications
(129 reference statements)
1
13
0
Order By: Relevance
“…The prevention of the altered insulin resistance markers observed in the GDM patients treated with the EVOO-enriched diet suggests that the EVOO dietary treatment is able to regulate insulin resistance, likely related to the concomitant reduction observed in maternal BMI. Although there are no previous studies addressing the effect of EVOO on insulin resistance markers in GDM, different studies performed out of pregnancy have shown the capacity of an EVOO-enriched diet to reduce parameters related to insulin resistance ( 12 , 49 ). Of note, as stated in our primary study, the nutritional indication to the GDM-EVOO group (3 tablespoons/day) was evaluated by nutritionists at least monthly, and good adherence (over 26 g EVOO per day at least 5 days a week) was reported in 83% of the patients ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of the altered insulin resistance markers observed in the GDM patients treated with the EVOO-enriched diet suggests that the EVOO dietary treatment is able to regulate insulin resistance, likely related to the concomitant reduction observed in maternal BMI. Although there are no previous studies addressing the effect of EVOO on insulin resistance markers in GDM, different studies performed out of pregnancy have shown the capacity of an EVOO-enriched diet to reduce parameters related to insulin resistance ( 12 , 49 ). Of note, as stated in our primary study, the nutritional indication to the GDM-EVOO group (3 tablespoons/day) was evaluated by nutritionists at least monthly, and good adherence (over 26 g EVOO per day at least 5 days a week) was reported in 83% of the patients ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of MD on MAFLD appear to be directly related to the ability of this dietary approach to modify many of the metabolic pathways underlying MetS, reducing cardiovascular risk and, overall, both morbidity and mortality of these patients [ 104 , 105 , 106 , 107 , 108 , 109 ]. Several studies have hypothesized that, although the effectiveness of the MD is nowadays consolidated, the true added value of this dietary approach in the treatment of MetS is connected to the intake of high doses of extra virgin olive oil (EVOO) [ 110 , 111 ].…”
Section: The Role Of Lifestyle Modificationsmentioning
confidence: 99%
“…The latter includes more than 30 different molecules: secoiridoids (the largest group, including oleacein and oleocanthal, along with aglycone forms of oleuropein and ligstroside), phenolic alcohols (mainly hydroxytyrosol (HT) and tyrosol (Tyr)), phenolic acids, lignans, and flavones. These ‘minor’ compounds are responsible for several of EVOO’s biological properties and sensory attributes (color, odor, flavor, taste, and aftertaste) [ 110 , 111 ].…”
Section: The Role Of Lifestyle Modificationsmentioning
confidence: 99%
“…Olive oil is rich in MUFAs in the form of oleic acid, with a content of 55-83%, but also α-linolenic acid (3-19%), phenolic compounds, sterols, tocopherols, polar pigments (pheophytins and chlorophylls), triterpenic, dialcohols and hydrocarbons, including squalene and the carotene β-carotene and xanthophylls [130]. Olive oil was reported to inhibit foodborne pathogens and stimulate useful microorganisms like L. acidophilus and B. bifidum, which are known as probiotic strains, with potential health benefits after consumption.…”
Section: Olive Oilmentioning
confidence: 99%